On the return on investment in education: the need for an unbiased assessment - Azqueta, Diego (2020)
Economic analysis provides some useful tools to assess the social profitability of education investment. The problem, however, is that they are too narrow in scope: in line with the Social Efficiency Ideology in this field they are only directed towards the goal of having a more productive labor force. Yet, a well-functioning society, also from an economic point of view, requires not only good workers but also well informed and participating citizens. And this is something that an education system based on this ideology, on the acquisition of an atomistic and specialized body of knowledge directed towards doing rather than knowing, will not procure. An approach to the education process partially based on the Social Reconstruction Ideology, emphasizing the importance of understanding the way society functions, the values that society holds, as well as the role of the citizen in this social fabric, is also required. The loss of this wider social perspective is illustrated by looking at the change in scope of the neoclassical model of growth.